Catalogue: Ancient Art - Anonymus, A.
of accessions 1985; esp. no. 2: Cylinder with incised decoration, bronze, Iran, Mannean, 9th-8th century B.C.; no. 18: Nesting quail stamp seal, Iran, Lake Van region, 4th-3rd millennium ?. ?.; no.24: Vase with relief decoration, terracotta, Hittite, 1400